Effects of monensin and sodium propionate on net nutrient absorption in steers fed high-grain diets - D.L. Harmon; T.B. Avery (Kansas Agricultural Experiment Station Research Reports, 1986)
Adding either monensin or sodium propionate alone or in combination to the diet of steers fed high-grain diets resulted in increased net absorption of glucose. Monensin reduced ammonia output and gut uptake of urea. We propose that increased propionate availability reduces the utilization of glucose by gut tissues. allowing more glucose to reach the portal system. These changes may contribute to the increased feed efficiency seen when monensin is fed.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Monensin; Sodium propionate; Steers; Diet